Design of Digital IIR Filter using Particle Swarm Optimization - Serbet, F.; Kaya, T.; Ozdemir, M. T. (Ieee, 2017)
The paper aims to establish a solution methodology for the optimal design of digital Infinite Impulse Response (IIR) filter by integrating the features of Particle Swarm Optimization (PSO). PSO is a method that optimizes a problem by iteratively trying to improve a candidate solution with regard to a given measure of quality to mathematical formula over the particle's position and velocity. The applied method explores the search space locally as well as globally and uses them in the mathematical formulas. The optimal design of IIR filter is realized with the result obtained with PSO.
40th International Convention on Information and Communication Technology, Electronics and Microelectronics (MIPRO) -- MAY 22-26, 2017 -- Opatija, CROATIA
Keywords: Filter Design; IIR filter; particle swarm optimization (PSO)